Fault reactivation in the Sierras Pampeanas resolved across Andean extensional and compressional regimes using thermochronologic modeling. (December 2021) - Ortiz, Gustavo; Stevens Goddard, Andrea L.; Fosdick, Julie C.; Alvarado, Patricia; Carrapa, Barbara; Cristofolini, Eber
Abstract: The reactivation of existing faults has long been recognized to control the location and style of deformation in orogenic systems including the Sierras Pampeanas in the southern Central Andes; however, it can remain difficult to resolve the timing and fault kinematics across multiple orogenic phases. In the Sierras Pampeanas, basement-cored range-bounding faults mark a Paleozoic terrane boundary and are seismically active; however, the protracted history of deformation along this lithospheric-scale regional fault system - located ~400 km from the plate boundary - has been poorly constrained. In this study, we present new apatite (U–Th-Sm)/He and fission track thermochronology data and thermal history models from ten samples from the Sierra de Valle Fértil-La Huerta in the Western Sierras Pampeanas of Argentina. The spatio-temporal patterns of rock heating and cooling identified by our thermal history models throughout this fault system are consistent with four discrete phases of deformation. Thermal patterns indicative of Mesozoic extensional deformation and latest Miocene - Pliocene compressional deformation corroborate previous interpretations of regional deformation episodes in the Sierras Pampeanas. Our study also identifies a period of middle-Miocene cooling that revises the location of the Andean thrust front. This episode of deformation was previously unrecognized in the Sierras Pampeanas and is contemporaneous with thin-skinned deformation in the adjacent Precordillera thrust belt. A Paleogene phase of cooling may also support a phase of compressional deformation in the Sierras Pampeanas during a period in which neutral tectonic conditions have been proposed along the Andean margin. Our findings outline a history of fault reactivation suggesting that the long-lived fault systems in the Sierras Pampeanas are sensitive to plate-margin processes. Highlights: Thermal modeling of AHe-AFT data records fault reactivation across orogenic cycles. Faults in the Sierras Pampeanas are highly sensitive to distal plate-boundary stress. Thermal record of Mesozoic extension preserved along Cenozoic reverse fault. Near-fault cooling shows multi-phase Cenozoic compression events. High Mio-Pliocene exhumation is identified in nearly all samples in the Sierra Valle Fértil-La Huerta.